COST AND PROFIT EFFICIENCY OF SOUTH - Siyaka, Nokuthula (My University, 2011)
The purpose of this study is to analyse the cost and profit efficiency of banks in South Africa. The cost-to-income ratio has always been used in the South African banking sector in measuring efficiency. However this approach is very simplistic and does not provide enough insight on real profit efficiency. This research uses a stochastic frontier model to determine both cost and profit efficiency of four large and four small, South African-based banks. The results of the study show that South African banks have significantly improved their cost efficiencies between 2000 and 2005. However efficiency gains on profitability, over the same time period, have not been significant. No bank was found to be superior to another in terms of achieving efficiency gains in cost reduction and profitability. A weak positive correlation was found to exist between the cost and profit efficiencies, with the most cost efficient banks also being most profit efficient. With regard to bank size, cost efficiency declined with increasing bank size
MBA - WBS
Keywords: Banks and banking